Yajnaseni : the story of Draupadi - "Ray, Pratibha" (New Delhi, 1995)
The undoubted heroine of the Mahabharata, one of the honoured 'pancha sati', one of the five most virtuous women in Hindu mythology, Draupadi is still seen by many as the woman responsible for the greatest war of all time. In this historical novel, Pratibha Ray makes an admirable attempt to present a balanced portrait of Draupadi and in doing so, skilfully brings to the forefront the deeper aspects of the character and mind of the remarkable Pandava Queen.
Keywords: Fiction - English